Metal–Organic‐Framework‐Supported Molecular Electrocatalysis for the Oxygen Reduction Reaction. Issue 15 (3rd March 2021) - Liang, Zuozhong; Guo, Hongbo; Zhou, Guojun; Guo, Kai; Wang, Bin; Lei, Haitao; Zhang, Wei; Zheng, Haoquan; Apfel, Ulf‐Peter; Cao, Rui
Abstract: Synthesizing molecule@support hybrids is appealing to improve molecular electrocatalysis. We report herein metal–organic framework (MOF)‐supported Co porphyrins for the oxygen reduction reaction (ORR) with improved activity and selectivity. Co porphyrins can be grafted on MOF surfaces through ligand exchange. A variety of porphyrin@MOF hybrids were made using this method. Grafted Co porphyrins showed boosted ORR activity with large (>70 mV) anodic shift of the half‐wave potential compared to ungrafted porphyrins. By using active MOFs for peroxide reduction, the number of electrons transferred per O2 increased from 2.65 to 3.70, showing significantly improved selectivity for the 4e ORR. It is demonstrated that H2 O2 generated from O2 reduction at Co porphyrins is further reduced at MOF surfaces, leading to improved 4e ORR. As a practical demonstration, these hybrids were used as air electrode catalysts in Zn‐air batteries, which exhibited equal performance to that with Pt‐based materials. Abstract : A variety of porphyrin@MOF hybrids were synthesized by grafting porphyrins on MOFs through ligand exchange. These hybrids showed boosted activity and significantly improved selectivity for the four‐electron reduction of oxygen. Zn‐air batteries assembled with these hybrids exhibited comparable performance to that with Pt‐based materials. Combining various molecular catalysts and MOFs is appealing to develop materials with diverse applications.